Applying Ho Chi Minh’s working style in current scientific research activities - Lê Đức Thọ (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The article studies Ho Chi Minh’s scientific working style, and at the same time, shows the application of Ho Chi Minh’s scientific working style in current scientific research. That working style always goes in-depth, researches, investigates and surveys thoroughly; work with programs and plans; work in association with inspection, review, and experience; work must always be innovative and creative, scientific work is not arbitrary, do not avoid negative and sensitive things.